Single-staged Surgical Correction of Kyphotic Deformity due to Dorsal Spinal Tuberculosis in Pediatric Patients: Outcome Analysis - Mageswaran Shanmugavelu; Makesh Ram Sriraghavan; Prabhu Aloy; Poornima Kumararaja; Sai Vinay Bharadwaj Namala (Journal of Orthopedics and Joint Surgery)
Introduction: Spinal tuberculosis (TB) is more commonly seen in individuals during the first three decades of life, but it can occur at any age. It can result in the collapse of the affected vertebrae, leading to deformities such as kyphosis and sagittal imbalance; the deformity and progression can be worse in the pediatric age-group due to their growth spurt. Neurological complications can occur when the tubercular infection affects the spinal cord or the nerve roots. This typically happens during the active stage of the disease or, in some cases, even after the infection has healed. The surgical approach to spinal TB indeed focuses on achieving specific objectives related to the infectious and structural aspects of the disease. The objective of treatment of kyphotic spinal TB in recent era is to achieve bacteriological quiescence by effective chemotherapy and correction of kyphotic deformity. Development in the field of diagnostic methods and imaging has allowed us to detect TB of the spine in less advanced stages of the disease in most cases. But in spite, few cases present with kyphotic deformity and neurological deficits. The issues that need careful discussion are the identification of children in whom kyphosis should be taken for correction and to reach a consensus on treatment when a patient presents with severe healed kyphosis with or without neural deficit. Materials and methods: We treated six patients with dorsal spinal TB with kyphotic deformity, of which two cases presented with paraparesis—managed by surgical decompression and posterior stabilization; all the cases were followed up periodically. Results: All six cases had good radiological and functional outcomes in terms of kyphotic correction and neurological recovery. There was a significant improvement in the mean kyphotic angle; the mean angle decreased from 34.33 (preoperative) to 11.22 degrees, one year after surgery. Conclusion: This study aimed to evaluate the clinical study efficacy and feasibility of one-stage posterior-only surgical treatment for thoracic spinal TB in adolescents. The multifaceted goals of surgery in spinal TB underscore the importance of a thorough understanding of the disease and a collaborative approach, and it ensures a comprehensive strategy. Thus posterior surgical method is effective in accomplishing debridement, obtaining satisfactory clinical results, correcting kyphotic deformity, and maintaining the correction.